2018
DOI: 10.1115/1.4039081
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Laminar Natural Convection in a Square Cavity With Wavy Wall and Horizontal Fin Attached to the Hot Wall

Abstract: Laminar natural convection in differentially heated square cavity with right cold wavy wall and horizontal conducting fin attached to its left hot wall has been investigated numerically. The vertical walls are maintained at different isothermal temperatures, while the horizontal walls are insulated. The fluid that filled the cavity is air with Prandtl number of 0.71. The investigation has been performed for Rayleigh number in the range of 103–106, the thermal conductivity ratio was varied from 10 to 105, three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The results indicated an increase in the both local and the mean Nu numbers as the heat source is lengthened. Kadari et al (2018) found that the distribution of temperature is notably dependent on the size of the heat source, and both average and local Nu numbers increase when the local heat source is extended.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated an increase in the both local and the mean Nu numbers as the heat source is lengthened. Kadari et al (2018) found that the distribution of temperature is notably dependent on the size of the heat source, and both average and local Nu numbers increase when the local heat source is extended.…”
Section: Introductionmentioning
confidence: 99%
“…Kadari et al [19] looked into laminar natural convection in a square hollow with a horizontal fin attached to hot wall and a cold wavy wall. The influence of fin length, number of undulations, thermal conductivity ratio and fin position were also studied.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations involving square cavities and enclosures of various sizes and aspect ratios have been carried out 20–37 …”
Section: Introductionmentioning
confidence: 99%
“…Several investigations involving square cavities and enclosures of various sizes and aspect ratios have been carried out. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Several researchers conducted a study on mixed convection inside cavities that were sinusoidal-heated, wherein Karim et al 38 conducted a numerical study of the unsteady mixed convection heat transfer properties of Ag-water nanofluids confined within a lid-driven square cavity with a sinusoidal heated bottom wall, according to the results the lower values of the parametric variation of sinusoidal even and odd frequency support enhanced heat transfer through convection and conduction.…”
Section: Introductionmentioning
confidence: 99%